Vulnerability of a coastal industrial community to sea level rise, hurricanes, and climate change - Abdelhafez, Mohamed, author; Mahmoud, Hussam, advisor; Ellingwood, Bruce R., advisor; Arneson, Erin, committee member (Colorado State University. Libraries, 2020)
Approximately 10% of the world's population live and work in low-lying coastal regions that are less than 10 meters above sea level, and this percentage is likely to increase during the remainder of the 21st century. Along with this growth is the potential for increasing economic losses due to hurricanes, storm surge and sea-level rise (SLR) in an era of climate change. More than 80% of global commodities are traded by sea. In the United States ports contributed $5.4 trillion to the U.S. economy, or approximately 26% of the GDP, and provided employment, either directly or indirectly, to over 30 million individuals. In this study, the potential impact of SLR on coastal communities are reviewed and critically appraised. A new model for quantifying the functionality of the seaports subject to various hurricanes, storm surge and sea level rise due to a changing climate is implemented in a fault tree analysis. A hydrodynamic analysis to enable the impact of tropical cyclones and SLR on port facilities is validated using data from Hurricane Katrina. A series of plausible hazard scenarios is identified and their impact on the Port of Mobile, AL is assessed. The key findings show that if a Katrina-like hurricane were to occur late in the 21st Century, the damages to the Port of Mobile, AL would be increased by 5.5 times and 6.5 times by SLR under RCP 4.5 and RCP 8.5 scenarios when compared to the damages caused by historical Hurricane Katrina alone. Furthermore, the immediate post-disaster functionality of the port under the RCP 8.5 scenario would be reduced to virtually zero.